Calculation of standards for permissible environmental impact for boilers with known technical characteristics - Askarova, A.S.; Safarik, P.; Bolegenova, S.A.; Mazhrenova, N.R.; Bolegenova, S.A.; Nugymanova, A.O. (Recent Contributions to Physics, 2020)
Emission of thermal power stations and boilers is regulated in accordance with the unified national regulatory requirements, taking into account the specifics of energy production, its life-sustaining function and is aimed at ensuring that air pollution is prevented as much as possible. The purpose of the regulation of emissions of thermal power plants is to limit its adverse impact on the air basin by developing, for the entire thermal power plant and each source of emissions on it, the maximum allowable emissions – control (in grams per second) and per annum (in tons per year), ensuring sanitary hygienic standards. Sanitary standards include the maximum permissible concentration, which reflects the level of components in the air that is safe for humans. In practice, several substances are simultaneously present in the air, the presence of which causes multicomponent air pollution. The atmospheric pollution index, which is calculated for a group of substances, is often used as a complex indicator of the degree of air pollution. Currently, mostly applied methods of component-wise assessment of atmospheric air quality are used in practice. When calculating atmospheric pollution by boiler houses, the total volumes of fuel combustion products are determined experimentally or by calculation. This article provides empirical formulas for calculating the above standards – the volume of flue gases, the maximum one-time emissions of ash, sulfur oxides, carbon and nitrogen for various boilers with known technical characteristics. Also, using the above formulas, a comparative analysis of the level of air pollution depending on the quality of various types of fuel burned in various types of boilers.